Perioperative search for circulating tumor cells in patients undergoing radical cystectomy for bladder cancer - Karl, A (BioMed Central, 2009)
OBJECTIVE: Despite having an organ confined tumor stage at the time of radical cystectomy, a certain number of bladder cancer patients will develop local or distant metastases over time. Currently there are no reliable serum markers for monitoring and evaluating risk profiles of urothelial cancers. Several studies suggest that detection of Circulating Tumor Cells (CTC) may correlate with disease status and prognosis at baseline and early in the treatment of cancers. The presence of CTCs in whole blood before and during radical cystectomy could provide further information on disease status, and could be used as an indicator to determine the need for adjuvant or even perioperative chemotherapy. METHODS: From 03/2009 to 05/2009, five patients with histologically proven transitional cell carcinoma of the urinary bladder participated in this study. All patients were admitted to the hospital for radical cystectomy (rCx). A standard or extended lymph node dissection was performed in all cases. Preoperative CT or MRI scans revealed no distant or local metastases. Median age was 66.8 years (55-81 yrs). After obtaining informed consent from each patient, approximately 30 mL of peripheral blood was taken immediately before rCx and again during surgical removal of the urinary bladder from the patients' body. As additional parameters, operation time (OR) for surgical removal of the bladder and the amount of blood volume that was used for the detection of CTCs were recorded. Obtained blood samples were processed using the Cell-Search System (Veridex(©)) within 48 hours of collection. CTCs were identified and quantitated using the Cell-Search System, followed by re-evaluation of the provided results by specially trained and experienced personal. (CS, SH) RESULTS: CTCs were detected before and during surgical removal of the urinary bladder in one of five patients (20%). In the one patient positive for CTC, two CTCs were detected in the blood sample that was obtained before surgery (analyzed blood volume was 25 mL). There was one CTC detected in the blood sample that was obtained during surgical removal of the urinary bladder (analyzed blood volume was 27 mL). There was no rise in the amount of CTCs during surgical procedure. The final pathological report of this patient showed an advanced tumor stage (T3b, N0, R1). In the other patients, no CTCs were detected at all, neither before rCX nor right after surgical removal of the bladder. Pathological stage for these patients ranged from pT1m G3 -pT2b G3. None of these patients showed lymph node involvement. An average of 14.6 lymph nodes (5-40 LNs) were obtained. OR time to surgical removal of the urinary bladder ranged from 60 minutes to 150 minutes (mean 82 min.). CONCLUSIONS: Although only a very small group of patients was analyzed in this study, the presence of CTCs seems to be correlated with an advanced tumor stage. Therefore the detection of CTCs could be used for an optimized assessment of a patient's disease status in urothelial cancer. A further aim of this study was to assess whether surgical manipulation during radical cystectomy is associated with a release of CTCs into the vascular system. None of the patients who were negative for CTCs before surgery showed CTCs during surgical removal of the bladder, suggesting that there was no release of CTCs during surgery. However, further study is needed to prove these findings and evaluate the significance of CTCs as an indicator for therapeutic decisions.